Perceived Authenticity, Empathy, and Pro-social Intentions evoked through Avatar-mediated Self-disclosures - Roth, Daniel; Bloch, Carola; Schmitt, Josephine; Frischlich, Lena; Latoschik, Marc Erich; Bente, Gary (ACM International Conference Proceeding Series, 2019)
Avatars are our digital embodied alter egos. Virtual embodiment by avatars allows social interaction with others using the full spectrum of verbal and non-verbal behaviour. Still, one’s avatar appearances is elective. Hence, avatars make it possible for users to discuss and exchange sensible or even problematic personal topics potentially hiding their real identity and hence preserving anonymity and privacy. While previous works identified similarities how participants perceive avatars compared to human stimuli, there is a question as to whether avatar-mediated self-disclosure is authentic and results in similar social responses. In the present study, we created a comparable stimulus set to investigate this issue and conducted an online study (N=172) for comparison. Our results indicate that avatars can be perceived as authentic and that empathy is attributed in similar level than to a human stimulus. In an exploratory model, we found that for in the overall results, authenticity fostered emotional empathy which in turn fostered pro-social intentions. We argue that avatars may serve as a valuable supporting medium for HCI applications related to mental well-being, self-disclosure, and support.
CRIS-Team Scopus Importer:2021-03-29
Keywords: Avatars; Empathy; Social Perception; Virtual Characters